Fuzzy Logic Controller Implementation for Motor DC Control Position With Real-Time Operating System - M Martin; Dodi Budiman Margana; Endang Habinuddin (IJISTECH (International Journal of Information System and Technology), 2023)
A fuzzy Logic Controller (FLC) is a control system that expresses in linguistics, there are several ways to defuzzification such as Sugeno. This paper proposes FLC to control the Motor DC Module position within -180 to 180 degrees using Real-Time Operating System (RTOS) running in the microcontroller. The FLC design based on input errors and changes of errors get from the feedback module, and defuzzification uses Sugeno rules. The FLC design simulates in the simulator program with the motor dc ideal model to show the output response transient. Experimental is done by using step input and variable inputs, step input is used to calculate the output response transient, and variable input to show the reliability of the control scheme. The output response shows that the motor DC control position has 0% of overshoot, 0.9 seconds of settling time, and 2.7769 rise time from position -80 to 0. The FLC success controls the position motor, and RTOS can be implemented in a microcontroller based on ATMega 2560 series.